Fuzzy Logic-Based Authentication Protocol for VANETs Networks - Abdulhussien, Israa Nasir (Iraqi Journal of Science, 2026)
The development of trust between vehicles in vehicular ad hoc networks (VANETs) serves as a fundamental requirement to guarantee application integrity while maintaining dependability. Reliability and trust allows vehicles to retrieve precise and dependable data from adjacent vehicles to perform the necessary decisions. Security remains difficult in VANET because it lacks central control and is characterized by dynamic operation methods. The main objective centers on developing more effective message verification systems. Since trust exists as a fuzzy concept, we implemented fuzzy logic to obtain trust values. The proposed system divides its functionality into two components which include a controller check stage built with four factors. Four factors establish the validity and legitimacy of vehicles in successful verification processes. Following the initial stage, the four factors proceed to the fuzzy system, allowing it to handle imprecise information and environmental uncertainties that exist during vehicle dynamics.